Preference Congruence, Information Accuracy, and Employee Performance: A Field Study - Maher, Michael W.; Ramanathan, Kavasseri V.; Peterson, Richard B. (Journal of Accounting Research, 1979)
The problem of motivating members of an organization to make decisions and to take actions that are congruent with the goals set by their superiors has been studied extensively. With costless incentive and information systems, the objective is to create incentives for subordinates to act in the best interests of those who determine the goals for the organization (e.g. owners, managers). However, with costly information and incentive systems, it may not always be optimal for an organization to remove goal conflicts.' In this paper, we report some results about the relationship between